2009
DOI: 10.1095/biolreprod.108.073577
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Induces Innate Antibacterial Responses in Human Trophoblasts via an Intracrine Pathway1

Abstract: The active form of vitamin D, 1,25-dihydroxyvitamin D (1,25(OH)2D), is a potent inducer of the antimicrobial protein cathelicidin, CAMP (LL37). In macrophages this response is dependent on intracrine synthesis of 1,25(OH)2D from precursor 25-hydroxyvitamin D (25OHD), catalyzed by the enzyme 25-hydroxyvitamin D-1alpha-hydroxylase (CYP27B1). In view of the fact that trophoblastic cells also express abundant CYP27B1, we postulated a similar intracrine pathway for induction of CAMP in the placenta. Analysis of pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
120
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(131 citation statements)
references
References 63 publications
8
120
0
1
Order By: Relevance
“…Coexpression of the receptor for 1,25(OH) 2 D 3 (vitamin D receptor [VDR]) in both decidua (9) and trophoblast (10) suggests that 1,25 (OH) 2 D 3 produced by the placenta may function in an autocrine or paracrine fashion. In support of this, recent studies by our group and others have shown that autocrine metabolism of 25OHD 3 to 1,25(OH) 2 D 3 promotes antibacterial and anti-inflammatory responses in maternal decidua (11) and fetal trophoblast (12,13). Such immunomodulatory actions of vitamin D are likely to be compromised under conditions of low maternal 25OHD 3 status, with potentially detrimental consequences for placental physiology.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Coexpression of the receptor for 1,25(OH) 2 D 3 (vitamin D receptor [VDR]) in both decidua (9) and trophoblast (10) suggests that 1,25 (OH) 2 D 3 produced by the placenta may function in an autocrine or paracrine fashion. In support of this, recent studies by our group and others have shown that autocrine metabolism of 25OHD 3 to 1,25(OH) 2 D 3 promotes antibacterial and anti-inflammatory responses in maternal decidua (11) and fetal trophoblast (12,13). Such immunomodulatory actions of vitamin D are likely to be compromised under conditions of low maternal 25OHD 3 status, with potentially detrimental consequences for placental physiology.…”
mentioning
confidence: 76%
“…However, it is important to recognize that vitamin D is also able to influence other aspects of immunity, notably the stimulation of antibacterial innate immune responses (18,22). In previous studies using human tissue, we have shown that induction of the antimicrobial protein cathelicidin by vitamin D is not restricted to the immune system but can also be observed with cells from both the maternal and fetal sides of the placenta (11,12). In future studies, it will be important to determine whether similar antibacterial mechanisms are also influenced by vitamin D in the placenta.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also important to recognize that novel mechanisms involving non-classical actions of vitamin D may further expand the role of vitamin D during pregnancy. In recent studies we have shown that vitamin D is a potent stimulator of innate antimicrobial responses to infection in human placental cells, whilst simultaneously inhibiting inflammation 155,156 . Given the link between infection, inflammation and risk of preterm birth 164 , it is tempting to speculate that vitamin D may have even broader beneficial effects in the general maintenance of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…It therefore seems likely that the high levels of local 1,25(OH) 2 D production within the placenta will impact on these antimicrobials. Studies in-vitro using human placenta tissue have shown that 25OHD and 1,25(OH) 2 D induce expression of cathelicidin in both maternal decidua 155 and fetal trophoblast 156 . In the latter case, vitamin D-induced cathelicidin expression promoted intracellular killing of Escherichia coli (E. coli), underlining the potential importance of vitamin D as a key mediator of placental response to infection 156 .…”
Section: Vitamin D and Infection And Inflammation During Pregnancymentioning
confidence: 99%
See 1 more Smart Citation